Viewpoint: Why "Open Source" Misses the Point of Free software. - Stallman, Richard (Communications of the ACM, 2009)
In this article the author discusses open source software. A history of the free computer software movement is given beginning in 1983 including the launch of the development of GNU (GNU's Not Unix), a free operating system. Topics include the ethical reasons behind the development of GNU and a group of people who broke off from the free software community to lobby for open source software.